Hare TRIM5α Restricts Divergent Retroviruses and Exhibits Significant Sequence Variation from Closely Related Lagomorpha TRIM5 Genes - Fletcher, Adam J. (American Society for Microbiology (ASM), 2010)
TRIM5α proteins recruit and restrict incoming cytoplasmic retroviruses. Primate TRIM5α sequence diversity underlies species-specific restriction and is likely caused by selective pressure from ancient pathogenic infections. Here we show that TRIM5α from the European brown hare restricts diverse retroviruses. Furthermore, it differs significantly in sequence from TRIM5α from the closely related rabbit, suggesting evolutionary changes in the last 12 million years since these species diverged. We propose that, like primates, lagomorphs have been subject to selective pressure from TRIM5-sensitive viruses, possibly related to the endogenous lentivirus RELIK found in both rabbits and hares.